Effectiveness of 0.1% Cyclosporine a Cationic Emulsion for Treating Dry Eye Disease After Cataract Surgery Analyzed Using a Placido Tear Film Analyzer - Song-A Che; Sang Beom Han; Yongwoo Lee (Diagnostics)
Background/Objectives: We aimed to evaluate the effectiveness of a 0.1% cyclosporin A cationic emulsion (CsA-CE) for dry eye disease (DED) post-cataract surgery using the DED index measured with a Placido tear film analyzer. Methods: We retrospectively reviewed the medical records of patients who underwent simple cataract surgery. All patients used 0.5% moxifloxacin and 1% prednisolone acetate eye drops four times daily postoperatively. They were divided into the CsA-CE and control groups based on whether they had used CsA-CE 1 week after surgery. Subjective and objective assessments were performed at the baseline and 1 month postoperation. The non-invasive tear meniscus height, non-invasive tear break-up time, conjunctival redness, meibomian gland morphology, and lipid layer thickness were assessed using the Keratograph 5M (Oculus). Results: No differences were observed in the preoperative dry eye parameters between the groups. The ocular surface disease index decreased from 19.26 to 14.58 (p = 0.046) at 1 month postoperation for the CsA-CE group, and the average non-invasive tear break-up time significantly increased from 10.97 to 13.00 s (p = 0.002). No such differences were observed for the control group. Nasal bulbar conjunctival hyperemia increased (p < 0.001) for the control group. Nasal limbal hyperemia and overall limbal hyperemia increased for both groups (CsA-CE, p = 0.005, 0.017; control, p = 0.001, 0.012). The lipid layer thickness increased from 70.29 to 86.41 nm for the CsA-CE group (p < 0.001), whereas no significant change was noted for the control group. Conclusions: CsA-CE (0.1%) is effective for treating DED after cataract surgery and improves the tear lipid layer.